The potentials and challenges of using fermentation to improve the sensory quality of plant-based meat analogs - Elhalis, Hosam; See, Xin Yi; Osen, Raffael; Chin, Xin Hui; Chow, Yvonne (Frontiers in Microbiology, 2023)
Despite the advancements made in improving the quality of plant-based meat substitutes, more work needs to be done to match the texture, appearance, and flavor of real meat. This review aims to cover the sensory quality constraints of plant-based meat analogs and provides fermentation as a sustainable approach to push these boundaries. Plant-based meat analogs have been observed to have weak and soft textural quality, poor mouth feel, an unstable color, and an unpleasant and beany flavors in some cases, necessitating search for efficient novel technologies. A wide range of microorganisms, including bacteria such as Lactobacillus acidophilus and Lactiplantibacillus plantarum, as well as fungi like Fusarium venenatum and Neurospora intermedia, have improved the product texture to mimic fibrous meat structures. Additionally, the chewiness and hardness of resulting meat analogs has been further improved through the use of Bacillus subtilis. However, excessive fermentation may result in a decrease in the final product's firmness and produce a slimy texture. Similarly, several microbial metabolites can mimic the color and flavor of meat, with some concerns. It appears that fermentation is a promising approach to module the sensory profiles of plant-derived meat ingredients without adverse consequences. In addition, the technology of starter cultures can be optimized and introduced as a new strategy to enhance the organoleptic properties of plant-based meat while still meeting the needs of an expanding and sustainable economy.